Molecular typing of Treponema pallidum causing early syphilis in China: a cross-sectional study - Peng, Rui-Rui; Yin, Yue-Ping; Wei, Wan-Hui; Wang, Hong-Chun; Zhu, Bang-Yong; Liu, Quan-Zhong; Zheng, He-Ping; Zhang, Jin-Ping; Huang, Shu-Jie; Chen, Xiang-Sheng (Sexually transmitted diseases, 2012)
There have been limited data on molecular epidemiology of syphilis in China. This study aimed to analyze strain type distribution of Treponema pallidum causing early syphilis across geographic areas in China using an enhanced method. Genital samples were collected from patients in East, South, and North China. Positive DNA of T. pallidum was analyzed by arp, tpr, and tp0548 genes. Sufficient DNA for full molecular typing existed in 197 of 324 samples, and 27 strain types were identified. A range of 3 to 20 repeats (except 4, 11, and 19 repeats) and 25 repeats were found for the 60-bp tandem repeats of the arp gene. This was the first time the 9 and 25 repeats were detected. For the RFLP analysis of the tpr genes, patterns a, d, h, j, and l were identified. This was the first time the h, j, and l patterns were observed in China. For the sequence analysis of the tp0548 gene, sequences c, e, and f were identified. Strain type distribution was significantly different across geographic areas (χ² = 20.6, P = 0.006). Overall, 14d/f was most predominant (39% of fully typed samples, 95% CI = 32%-46%); 13d/f, 15d/f, and 16d/f were next most common (each 13% of fully typed samples, 95% CI = 9%-18%). There is substantial genetic diversity of T. pallidum in China. The broad and ununiform distribution of strain types may reflect differences in regional sexual network patterns. Predominance of few strain types may indicate a linked transmission.